The Importance Of English Skills For Heavy Equipment Engineering Students At The Olat Maras Community Academy - Musmulyadin, Musmulyadin; Soviya, Ovi; Asmadi, Asmadi; Novriani, Nova (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The existence of the English language has always been an interesting topic for everyone because it plays an important role in one's career and in fulfilling job opportunities. Employees who are proficient in English in a company earn higher wages than those who cannot speak English. The heavy equipment engineering study program at the Olat Maras Community Academy is a technology study program and the language used is English, such as in manuals, instructions and terms in heavy equipment engineering. Heavy equipment engineering graduates have English language skills, which greatly increases their chances of being accepted for jobs offered by companies. Being able to communicate in English and operate heavy equipment are very strategic for improving one's standard of living. The purpose of this study is to determine the perceptions of students in the heavy equipment engineering study program at the Olat Maras Community Academy. The method used in this research is qualitative, using a descriptive quantitative approach to analyse the research data obtained. The results show that 92.8% of heavy equipment engineering students are aware that English plays an important role for heavy equipment engineering students at the Olat Maras Community Academy in supporting their careers. Students of the heavy equipment engineering study program at the Olat Maras Community Academy are not satisfied with their skills but also English language skill.